cho hàm số y=2/3x^3-mx^2-2(m^2-1)x+2/5. tìm m để hàm số có 2 điểm cực trị.thỏa mãn: 2(x1+x2)+(x1.x2)=1 17/07/2021 Bởi Athena cho hàm số y=2/3x^3-mx^2-2(m^2-1)x+2/5. tìm m để hàm số có 2 điểm cực trị.thỏa mãn: 2(x1+x2)+(x1.x2)=1
Đáp án: $\begin{array}{l}y = \dfrac{2}{3}{x^3} – m{x^2} – 2\left( {{m^2} – 1} \right)x + \dfrac{2}{5}\\ \Rightarrow y’ = 2{x^2} – 2mx – 2\left( {{m^2} – 1} \right) = 0\\ \Rightarrow {x^2} – mx – {m^2} + 1 = 0\left( * \right)\\ \Rightarrow \Delta > 0\\ \Rightarrow {m^2} – 4\left( { – {m^2} + 1} \right) > 0\\ \Rightarrow 5{m^2} – 4 > 0\\ \Rightarrow {m^2} > \dfrac{4}{5}\\ \Rightarrow \left[ \begin{array}{l}m > \dfrac{{2\sqrt 5 }}{5}\\m < – \dfrac{{2\sqrt 5 }}{5}\end{array} \right.\\Theo\,Viet:\left\{ \begin{array}{l}{x_1} + {x_2} = m\\{x_1}{x_2} = – {m^2} + 1\end{array} \right.\\2\left( {{x_1} + {x_2}} \right) + {x_1}{x_2} = 1\\ \Rightarrow 2m – {m^2} + 1 = 1\\ \Rightarrow {m^2} – 2m = 0\\ \Rightarrow m\left( {m – 2} \right) = 0\\ \Rightarrow \left[ \begin{array}{l}m = 0\left( {ktm} \right)\\m = 2\left( {tm} \right)\end{array} \right.\\Vay\,m = 2\end{array}$ Bình luận
Đáp án:
$\begin{array}{l}
y = \dfrac{2}{3}{x^3} – m{x^2} – 2\left( {{m^2} – 1} \right)x + \dfrac{2}{5}\\
\Rightarrow y’ = 2{x^2} – 2mx – 2\left( {{m^2} – 1} \right) = 0\\
\Rightarrow {x^2} – mx – {m^2} + 1 = 0\left( * \right)\\
\Rightarrow \Delta > 0\\
\Rightarrow {m^2} – 4\left( { – {m^2} + 1} \right) > 0\\
\Rightarrow 5{m^2} – 4 > 0\\
\Rightarrow {m^2} > \dfrac{4}{5}\\
\Rightarrow \left[ \begin{array}{l}
m > \dfrac{{2\sqrt 5 }}{5}\\
m < – \dfrac{{2\sqrt 5 }}{5}
\end{array} \right.\\
Theo\,Viet:\left\{ \begin{array}{l}
{x_1} + {x_2} = m\\
{x_1}{x_2} = – {m^2} + 1
\end{array} \right.\\
2\left( {{x_1} + {x_2}} \right) + {x_1}{x_2} = 1\\
\Rightarrow 2m – {m^2} + 1 = 1\\
\Rightarrow {m^2} – 2m = 0\\
\Rightarrow m\left( {m – 2} \right) = 0\\
\Rightarrow \left[ \begin{array}{l}
m = 0\left( {ktm} \right)\\
m = 2\left( {tm} \right)
\end{array} \right.\\
Vay\,m = 2
\end{array}$